Interfacial engineering with amino-functionalized graphene for efficient perovskite solar cells. Issue 35 (15th August 2016) - Wen, Xiaoru; Wu, Jiamin; Gao, Di; Lin, Changjian
Abstract : In pursuit of reducing the surface trap states of perovskite as well as enhancing the hole control of dopant-free spiro-OMeTAD, an amino-rich graphene (NGs) was introduced via a facial solution method as an interlayer at the perovskite/HTM interface. Abstract : In pursuit of reducing the surface trap states of perovskite as well as enhancing the hole control of dopant-free spiro-OMeTAD, an amino-rich graphene (NGs) was introduced via a facial solution method as an interlayer at the perovskite/HTM interface. A number of characterizations, including photoluminescence and impedance spectroscopy, was conducted to reveal the interfacial effect of the NGs, and it was demonstrated that the amino group facilitated the reduced surface trap of perovskite and that graphene could behave as an efficient hole extraction and transfer pathway through the HTM network. Consequently, a maximum PCE of 14.6% could be obtained, which represented a remarkable improvement of ca. 36% over the control device (10.7%), with the improvement mainly related to the increase of J SC and FF.